Coopetition Segments in a Public-Sector Context: Insights from a Business Region. Issue 13 (3rd October 2018) - Stentoft, Jan; Mikkelsen, Ole Stegmann; Ingstrup, Mads Bruun
ABSTRACT: The concept of coopetition is well-known in a private-sector context, but it is greatly neglected in a public-sector context. In continuation of this, the article sets out to explore and further position coopetition in the public sector. This is achieved through a study of coopetition among seven municipalities located in a Danish business region named the Triangle Region. The article concludes by identifying and describing four public-sector coopetition segments, and by providing a segmentation model to categorize and discuss different coopetition initiatives. Furthermore, the model can help public servants and politicians to prioritize coopetition initiatives and visualize their complexity.